HUBUNGAN INTERAKSI TEMAN SEBAYA DENGAN PERILAKU ASOSIAL PADA ANAK DI TK NEGERI PEMBINA PONTIANAK - Ningsih, Sri Rahayu; Ali, Muhamad; Yuniarti, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
This study aims to find out about the relationship of peer interaction with asocial behavior in 5-6 year olds in the West Pontianak State Kindergarten. Using a quantitative approach and descriptive-quantitative methods with parallel correlation study studies. The sample in this study were 16 children in group B1 and 16 children in Group B2. Data collection techniques used are observation and documentation methods. Data collection tools in this study use a rating scale that is with Likert Scale. While the analysis technique used in this study is the analysis of Product Moment Correlation. Based on the results of data analysis about the relationship of peer interaction with asocial behavior in children aged 5-6 years in Taman-Kan the West Pontianak State Trustees showed that the r_ (count) value was -0.390. As for the r_ value (table) of 0.361. Because the value of r_ (count) Ëƒr_ (table) (- 0.390 Ëƒ 0.361), then the null hypothesis is rejected. This means that there is a significant relationship between peer interaction with asocial behavior in children aged 5-6 years in kindergarten State West Pontianak coaches, with a negative correlation direction which means that if the interaction with friends is high / good then asocial behavior will decrease or decrease . The conclusion is that there is a significant relationship between peer interaction with asocial behaviorÂ Keywords: Peer Interaction, Asocial BehaviorÂ